SAT0559 Systematic literature review (SLR) for the 2018 update of the eular management recommendations for hand osteoarthritis (OA). (12th June 2018) - Kroon, F.; Kloppenburg, M.; Schoones, J.; Carmona, L.
Abstract : Background: As part of the update of the EULAR management recommendations an SLR of available evidence for hand OA treatment was performed. Objectives: To inform the task force of an overview of available evidence for the efficacy and safety of all non-pharmacological, pharmacological and surgical interventions for hand OA. Methods: We searched Medline, EMBASE, Cochrane Central, and 2016–2017 conference abstracts until June 2017 for (randomised) controlled trials or Cochrane reviews. Observational studies with a comparator were included to assess safety, or effects of surgical interventions. Main efficacy outcomes were pain, function, and hand strength. Risk of bias was assessed. Meta-analysis was performed if possible. Results: Of 7036 records, 127 references were included, of which 50 studies concerned non-pharmacological, 64 concerned pharmacological, and 12 concerned surgical interventions. Most trials were published after 2007. Many studies were at high risk of bias, mainly due to inadequate randomisation or lack of blinding. Overall, effect sizes of effective therapies were small. Beneficial non-pharmacological treatments for pain relief include hand exercise, and prolonged splinting of the thumb base (Table). A single trial showed that assistive devices had no effect on pain, but led to functional improvements (mean difference (MD) −0.3, 95% confidence interval (CI) −0.6;0.01 on AUSCAN function, range 1–5). Topical and oral non-steroidal anti-inflammatory drugs (NSAIDs) proved equally effective for pain relief (Table), while topical NSAIDs led to less adverse events (e.g., risk ratio for withdrawals due to adverse events 0.15, 95% CI 0.03;0.63). Single trials demonstrated beneficial effects for other pharmacological interventions, including chondroitin sulphate, and intra-articular (i.a.) glucocorticoid injections in interphalangeal joints (Table). Compared to placebo, no beneficial effects were demonstrated for i.a. glucocorticoid or hyaluronic acid injections in the thumb base, hydroxychloroquine, or tumour necrosis factor inhibitors (Table). In two trials, structure modification was the primary outcome measure, though no disease-modifying properties were found in these studies. In a Cochrane review no surgical intervention for thumb base OA appeared more effective than another, although in general, more complex procedures led to more complications. Conclusions: The number of trials in hand OA has steeply increased over the last decade, providing evidence for several therapeutic options for symptom relief, though no disease-modifying drugs have yet been found. High-quality trials investigating often used analgesics like paracetamol are needed. Disclosure of Interest: None declared